2022
DOI: 10.7759/cureus.23390
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antithrombotic Therapy on the Outcome of Patients Undergoing Laparoscopic Colorectal Cancer Surgery: A Systematic Literature Review

Abstract: In recent years, many operations have been performed as laparoscopic surgeries in the field of gastrointestinal surgery, but the effect of antithrombotic therapy (ATT) on hemorrhagic complications in patients who have undergone laparoscopic colorectal cancer surgery remains unknown. In addition, the efficacy and safety of pharmacotherapy for the prevention of venous thromboembolism (VTE) have not yet been concluded. The purpose of this systematic review study is to clarify the effect of ATT on hemorrhagic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A recent cohort research of 3072 patients receiving major digestive surgery showed that continuing aspirin monotherapy before surgery substantially decreased the risk of thromboembolism in those undergoing APT 4 . Nevertheless, most studies assessing perioperative APT management are patient registries or retrospective sub-analyses, 5–8 and clinical practice varies greatly as regards perioperative antithrombotic regimens 9–13 . This study showed that in patients receiving antiplatelet medication, continued preoperative aspirin therapy substantially lowers the likelihood of thromboembolic consequences.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…A recent cohort research of 3072 patients receiving major digestive surgery showed that continuing aspirin monotherapy before surgery substantially decreased the risk of thromboembolism in those undergoing APT 4 . Nevertheless, most studies assessing perioperative APT management are patient registries or retrospective sub-analyses, 5–8 and clinical practice varies greatly as regards perioperative antithrombotic regimens 9–13 . This study showed that in patients receiving antiplatelet medication, continued preoperative aspirin therapy substantially lowers the likelihood of thromboembolic consequences.…”
Section: Discussionmentioning
confidence: 77%
“…4 Nevertheless, most studies assessing perioperative APT management are patient registries or retrospective sub-analyses, [5][6][7][8] and clinical practice varies greatly as regards perioperative antithrombotic regimens. [9][10][11][12][13] This study showed that in patients receiving antiplatelet medication, continued preoperative aspirin therapy substantially lowers the likelihood of thromboembolic consequences. Hence, preoperative continuation of single aspirin therapy is one of the best strategies to avoid major thromboembolic complications after elective gastroenterological surgery in patients undergoing APT.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations